Maps of JICA Major Projects - JICA (Japan International Cooperation Agency (JICA), 2022)
Maps of JICA Major Projects
Keywords: #Map / Mapa; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

Actualidade Económica de Moçambique: Preparação para Recuperação (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~!!.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Mozambique Economic Update : Setting the Stage for Recovery (World Bank Group, 2021)
The global pandemic has taken a heavy toll on Mozambique’s economy. In 2020, the country experienced its first economic contraction in nearly three decades. COVID-19 (coronavirus) hit the economy as it was attempting to recover from the slowdown triggered by the hidden debt crisis and the tropical cyclones in 2019. Real gross domestic product (GDP) contracted by 1.3 percent in 2020, compared to a pre-Covid estimate of 4.3 percent, as external demand declined, domestic lockdown measures disrupted supply chains and depressed domestic demand, and liquified natural gas (LNG) investments were delayed. COVID-19 has caused a sudden income loss for enterprises and households, worsening living conditions, especially for the urban poor largely engaged in the informal sector. According to the National Institute of Statistics, as of June 2020, about 120,000 jobs were lost and 63,000 employment contracts suspended, with women being the most affected. Around 3 percent of the firms affected were forced to cease their activity. Services activities are the hardest hit. The tourism and hospitality industries have particularly suffered a steep decline in revenues. COVID-19 has jeopardized years of hard-won development gains, with about one million people estimated to have slipped into poverty in 2020 (as measured by the international poverty line of 1.90 US Dollars per day). While there is great uncertainty about the path of the pandemic, the economy is expected to gradually recover from 2021 as aggregate demand rebounds and LNG investments and extractive production gain momentum. Despite the expected recovery, the widespread deployment of COVID-19 vaccines will be at the core of a resilient recovery. This Economic Update explores the implications of COVID-19 for the economy, businesses and households. It makes recommendations for moving forward—in the short-term relief phase, as well as over the medium and longer term in order to 'build back better~!!.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; economic development / desenvolvimento económico; health - COVID-19 / saúde – COVID-19; health / saúde; private sector / setor privado

Mozambique - Combined Mid-Term Review of the Country Strategy Paper 2018-2022 and Country Portfolio Performance Review 2020 (African Development Bank, 2021)
The Bank Group’s Country Strategy Paper (CSP) 2018-2022 for Mozambique was approved by the Boards of Executive Directors in June 2018. The CSP was prepared in a context of economic downturn triggered by the deterioration of the country's financial situation and scaleddown dialogue between the Government of Mozambique (GoM) and Donor Partners (DPs). The CSP was anchored on two pillars: (i) "Development of infrastructure to enable transformative, inclusive growth and job creation", and (ii) "Support to agricultural transformation and value chain development".
Publisher: African Development Bank Group
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

Project for Construction of Bridges on N380 in Cabo Delgado - JICA (2020)
Project outline Project Overview： - This project is to secure smooth and safe connectivity at the road N380 (Sunate - Oasse) through reconstruction of bridges, Messalo1 (45m)/ Messalo-3 (60m)/ Mapuede (45m), thereby contributing to facilitate the economy of Cabo Delgado and neighboring countries
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; infrastructure / infrastrutura

Donor relations and sovereignty - Flentø, Johnny; Simao, Leonardo Santos (2020)
As a sovereign country, Mozambique initially relied on international solidarity and managed its donor relations well. Donor dependency entailed some loss of agency for the government as it allowed donors to challenge its capacity but never its authority. However, in the last decade, donor countries have expressed disappointment with reforms and challenged the government’s legitimacy. This is not only because of developments in Mozambique. Donor countries have become less enthusiastic about long-term, harmonized development cooperation and less concerned with aid effectiveness for poverty alleviation and inclusive growth. Aid budgets are under pressure and development finance is linked more to other donor countries’ foreign policy concerns, especially security and commerce. Mozambique should expect increasing instrumentalization of aid budgets by donors. It must be able to address its partners’ concerns other than those of poverty alleviation, human rights, and democracy and carefully weigh conflicting interests of its partners against its own long-term interests. The institutions Mozambique developed to deal with donors are not well suited to today’s challenges. They focus on less relevant areas of the relationship with foreign countries, which often serve other agendas. Reforms could start with strengthening Mozambique’s foreign service as a genuine coordinator of foreign relations and the establishment of greater discipline around national plans and strategies. Institutionalizing strong links between the foreign ministry and key economic ministries under the leadership of the prime minister could help.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo

Relações com os doadores e soberania - Flentø, Johnny; Simao, Leonardo Santos (2020)
Como país soberano, Moçambique confiou inicialmente na solidariedade internacional e geriu bem as suas relações com os doadores. A dependência em relação a estes implicou que o Governo experimentasse alguma perda de capacidade de intervenção, permitindo que os doadores desafiassem a sua competência, embora nunca a sua autoridade. No entanto, na última década, os países doadores expressaram o seu desapontamento com as reformas e contestaram a legitimidade do Governo. Isto não se deve apenas aos desenvolvimentos ocorridos em Moçambique. Os países doadores ficaram menos entusiasmados com a cooperação para o desenvolvimento harmonizada a longo prazo e menos preocupados com a eficácia da ajuda ao desenvolvimento no alívio da pobreza e no crescimento inclusivo. Os orçamentos de ajuda ao desenvolvimento estão sob pressão e o financiamento do desenvolvimento está mais ligado às preocupações de política externa de outros países doadores, especialmente nas áreas da segurança e do comércio. Moçambique deve esperar uma instrumentalização crescente dos orçamentos de ajuda ao desenvolvimento por parte dos doadores. E deve ser capaz de abordar as preocupações dos seus parceiros para além da redução da pobreza, dos direitos humanos e da democracia e ponderar cuidadosamente o conflito entre os interesses dos seus parceiros e os seus próprios interesses a longo prazo. As instituições que Moçambique desenvolveu para lidar com os doadores não estão adequadamente adaptadas aos desafios actuais. Concentram-se em áreas menos relevantes da relação com países estrangeiros, que muitas vezes servem outras agendas. As reformas poderiam começar pelo reforço do serviço de política externa de Moçambique como um verdadeiro coordenador das relações externas e pelo estabelecimento de uma maior disciplina em torno de planos e estratégias nacionais. Uma ajuda poderia ser a institucionalização de ligações fortes entre o Ministério dos Negócios Estrangeiros e os principais ministérios económicos sob a liderança do primeiro-ministro.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; economic development / desenvolvimento económico; inclusive growth / crescimento inclusivo

Republic of Mozambique Joint World Bank-IMF Debt Sustainability Analysis - IDA; IMF (International Development Association (IDA) and the International Monetary Fund (IMF), 2020)
Mozambique’s debt remains in distress, which is unchanged from the previous DSA published in June 2019. Consideringthat, to a large extent, future borrowingand governmentguarantees reflect state participation in the sizable liquified natural gas (LNG) development, debt is deemed sustainable in a forward-looking sense. Participation in the recently announced G20 initiative would provide debt service relief in the near term, thus flattening the projected sharp deterioration in debt liquidity indicators due to the COVID-19 pandemic. The possibility of an extension of the G20 initiative into 2021 would be a further mitigating factor for the debt sustainability assessment. The present value (PV) of external public and publicly guaranteed (PPG) debt relative to GDP is projected to remain above the prudent threshold with a gradual declining path dropping below the threshold by 2028.The PV of PPG external debt relative to exports would drop below the prudent threshold in 2024. The ratio of external public debt service to fiscal revenues would drop below the prudent threshold temporarily in 2020 but would breach again the threshold until 2030. The debt service-to-exports ratio would remain around the prudent threshold until 2023, when it drops and remains below the threshold for the rest of the projection period.
Keywords: *tagged; FDI - foreign direct investment / IDE - investimento directo estrangeiro; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; economic development / desenvolvimento económico

Additional Financing to the Agriculture and Natural Resources Landscapes Management Project (SUSTENTA) - World Bank (World Bank, 2019)
Proposed Development Objective(s) Parent The project development objective is to integrate rural households into sustainable agriculture and forest-based value chains in the Project area and, in the event of an Eligible Crisis or Emergency, to provide immediate and effective response to said Eligible Crisis or Emergency. Components Agriculture and Forest-Based Value Chain Development Securing Land Tenure Rights and Increasing Natural Resources Resilience Project Coordination and Management Contingency Emergency Response
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; governance / governação; land governance / gestão de terra; natural resources / recursos naturais

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Sah, Anjali; Le, Ha (IDS, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies (IDS)-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to US$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

Actualidade Económica de Moçambique: Transitando para um crescimento mais inclusivo (World Bank Group, 2018)
Buoyed by a drop in inflation and the advancement of one of two major gas projects, the Mozambique Economic Update (MEU): Shifting to Inclusive Growth notes that the country is more stable since the 2016 debt crisis triggered the economic slump, but growth prospects are limited. Gross domestic product (GDP) growth was an average 3.8% in 2016 and 2017 and is expected to reach a slightly lower rate of 3.3% in 2018. Services such as tourism, transport and finance—all hardest hit by the crisis—have shown a modest increase in growth, the report says, however these gains were offset by slowed growth in the extractives sector. Mozambique’s growth opportunities also hinge on the recovery of consumer spending, especially in services, which had been the largest driver of growth before 2016, the report notes. A strong policy focused on reducing macroeconomic uncertainty and enhancing investment would help lay the foundation for complete recovery and more inclusive growth, the report says.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; inclusive growth / crescimento inclusivo

Mozambique Economic Update: Shifting to More Inclusive Growth (World Bank Group, 2018)
Buoyed by a drop in inflation and the advancement of one of two major gas projects, the Mozambique Economic Update (MEU): Shifting to Inclusive Growth notes that the country is more stable since the 2016 debt crisis triggered the economic slump, but growth prospects are limited. Gross domestic product (GDP) growth was an average 3.8% in 2016 and 2017 and is expected to reach a slightly lower rate of 3.3% in 2018. Services such as tourism, transport and finance—all hardest hit by the crisis—have shown a modest increase in growth, the report says, however these gains were offset by slowed growth in the extractives sector. Mozambique’s growth opportunities also hinge on the recovery of consumer spending, especially in services, which had been the largest driver of growth before 2016, the report notes. A strong policy focused on reducing macroeconomic uncertainty and enhancing investment would help lay the foundation for complete recovery and more inclusive growth, the report says.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; inclusive growth / crescimento inclusivo

Mozambique Country Strategy Paper 2018 -2022. Supporting Mozambique towards the HIGH5s - Santos, Almeida (African Development Bank, 2018)
The African Development Bank Group’s Country Strategy Paper (CSP) 2018-22 for Mozambique comes at a time when the country adopted its long term development strategy ‘ENDE’ 2015-35. The CSP was prepared on the basis of extensive consultations held with the Government of Mozambique, Development Partners, the private sector and the civil society. The main objective of the ENDE is the improvement of the livelihoods of the population through the structural transformation of the economy, and the expansion and diversification of national production. The strategy is to be implemented through the 5-Year Government Programs (PQGs). The PQG goal for 2015-19 is to increase employment, productivity and competitiveness to improve living conditions of Mozambicans, in an environment of peace, harmony and tranquillity, while consolidating democracy and inclusive participatory governance.
Keywords: G - Mozambique / Moçambique; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

The Project for Supporting the Promotion of Nacala Corridor Development - Final Report - Japan International Cooperation Agency (JICA) (Japan International Cooperation Agency (JICA), 2018)
Final JICA report on Nacala Corridor Development Project, whose objectives include: to clarify organizations for promoting and coordinating the implementation of development strategies for the Nacala Corridor Region in accordance with PEDEC-Nacala and to prepare for the implementation of high priority projects in accordance with PEDEC-Nacala. The study project commenced in April 2012 and the final study report was produced in April 2015.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Lichinga; GP - Cabo Delgado; GP - Nampula; GP - Niassa; GP - Tete; GP - Zambézia; L - english / inglês; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura; natural resources / recursos naturais; private sector / setor privado

Moçambique Avaliação de Pobreza: Crescimento Forte, Mas Não Partilhado (World Bank Group, 2018)
Mozambique has experienced strong and sustained economic growth in the last two decades. Growth of its Gross Domestic Product (GDP) expanded at an annual average rate of 7.2 percent between 2000 and 2016, making it one of the fastest-growing countries in Sub-Saharan Africa (SSA). The economic expansion has boosted incomes and living standards. GDP per capita, for instance, grew annually on average by 4 percent over the same period, climbing from 561 US dollars to 1,128 US dollars (2011 PPP). Growth has been supported by a rebounding agricultural sector, particularly in the first phase of the post-war period, increased productivity in trade, transport and communications and financial services, sound macroeconomic management, large-scale foreign investments projects and significant donor support. More recently, however, growth has slowed down due mainly to macroeconomic factors and severe natural disasters.
Keywords: *tagged; G - Mozambique / Moçambique; L - portuguese / português; development partners / parceiros de cooperação; poverty / pobreza

Mozambique Poverty Assessment: Strong But Not Broadly Shared Growth (World Bank Group, 2018)
Mozambique has experienced strong and sustained economic growth in the last two decades. Growth of its Gross Domestic Product (GDP) expanded at an annual average rate of 7.2 percent between 2000 and 2016, making it one of the fastest-growing countries in Sub-Saharan Africa (SSA). The economic expansion has boosted incomes and living standards. GDP per capita, for instance, grew annually on average by 4 percent over the same period, climbing from 561 US dollars to 1,128 US dollars (2011 PPP). Growth has been supported by a rebounding agricultural sector, particularly in the first phase of the post-war period, increased productivity in trade, transport and communications and financial services, sound macroeconomic management, large-scale foreign investments projects and significant donor support. More recently, however, growth has slowed down due mainly to macroeconomic factors and severe natural disasters.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; poverty / pobreza

Country Results Brief 2018 - Mozambique - African Development Bank (African Development Bank, 2018)
Over the last decade, Mozambique has been one of the fastest-growing African economies, enjoying average economic growth of about 8% between 2004 and 2015. It received strong support from the international community during the period (for example, in 2014 it received US$2 billion in official development assistance). In parallel, the country has embarked on major reforms — especially fiscal reforms and tax administration — and has opened up to foreign investment, particularly for the exploitation of its natural resources.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; governance / governação; infrastructure - energy / infrastrutura - energia; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura; private sector / setor privado

Mozambique Urbanization Review: Accelerating Urbanization to Support Structural Transformation in Mozambique (World Bank Group, 2017)
The Mozambique Urbanization Review aimed at contributing to the country’s policy and institutional reform agenda on how to harness the full potential of urbanization to promote economic growth and poverty reduction. The study carried out in-depth analyses of the urbanization process, uncovering how urbanization has been influenced by national, regional, and international factors. It identified and analyzed key policy and institutional constraints in increasing the economic benefits of urbanization, including economic, transport, land, and decentralization policies. The study concluded that faster urbanization could increase the pace of economic growth and poverty reduction, but this should not be achieved at the expenses of investments in rural development and agriculture. However, constraints in the creation of productive urban jobs, limited connectivity throughout the system of cities, and dysfunction urban land markets have undermined its economic outcomes. Based on the main findings, the study proposed an emerging national urban reform agenda to enhance the benefits from urbanization in Mozambique focused on: (i) strengthening rural-urban linkages, including reforms to local government finances, enhancing trade and commuting flows; (ii) making urban land systems more equitable and efficient; and, (iii) deepening decentralization to provide a broader remit to municipalities for urban planning and domestic resource mobilization.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; urbanization / urbanização

JICA in Mozambique Brochure - Japan International Cooperation Agency (JICA) (2016)
1. What is JICA? Since joining the Colombo plan in 1954, Japan has been providing financial and technical assistance to developing countries through ODA (Official Development Assistance). JICA is the "one stop shop of Japan's bilateral ODA'', providing Technical Cooperation, ODA Loans (Concessional Loans) and Grant Aid. JICA has a network of more than 90 overseas offices. In Mozambique, JICA opened office in 2003. 3. Priority Areas in Mozambique: 1) Activation of Regional and Local Economies 2) Environment and Climate Change Action 3) Human Development & Capacity Building
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação

Civil society organisations’ political control over Brazil and Japan’s development cooperation in Mozambique: More than a mere whim? - Chichava, Sérgio; Durán, Jimena (LSE, 2016)
This article aims to analyse and explain the reasons behind the CSOs’ strong criticism of the ProSavana programme. This will contribute toward: (1) understanding the role of Mozambican CSOs as actors regulating international development cooperation projects; (2) revealing the political and economic interests behind ProSavana, as a first step toward a more critical approach to trilateral cooperation; and (3) illustrating through this case how a partnership between Brazil and “traditional” donors actually works. Firstly, we will analyse the cooperation policies of Brazil and Japan in Mozambique, taking into account its evolution, actors, mechanisms and motives. Secondly, we will introduce ProSavana, examining the narratives and roles of Japan and Brazil in this programme. Thirdly, we will consider the engagement of CSOs from the three countries, their role in exerting a political check on the Brazilian and Japanese governments, investors, and companies, as well as their narratives and mechanisms of protest.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; agriculture / agricultura; civil society / sociedade civil; development partners / parceiros de cooperação

Ex-Post Project Evaluation 2014 (Mozambique, Bhutan, Palestine) - JICA (Japan International Cooperation Agency (JICA), 2015)
The project’s objective was to improve access to lower secondary education, by constructing 4 schools and extending the capacity of existing schools and their facilities in the target areas of Maputo Province and Gaza Province, thereby contributing to improvement of the quality of education. The project’s objective coincides with the development policy of Mozambique, which emphasizes the expansion of access to secondary education at the time of planning and also ex-post evaluation. It also coincides with the development needs of Mozambique, because there are very strong needs for the construction of secondary schools in order to respond to the rapid increase in the number of students who wish to receive secondary education. It was also relevant to Japan’s ODA policy at the time of planning. Thus, its relevance is high. The project cost and the project period are the same as planned, thus its efficiency is high. As to the effects of the project, 4 schools and 58 classrooms were constructed as planned, the number of students enrolled at those schools exceeded the original target, and other positive effects were revealed in terms of the access to secondary education such as improvement of educational environment and reduction in commuting time to schools. Thus, its effectiveness is high. There were some negative impacts of the project; for example, the IT classrooms of some schools were not utilized as planned, and the promotion rate declined in some grades of 2 schools in Maputo Province partly because the number of students per classroom far exceeded the capacity of the classroom. On the other hand, there were some positive indirect impacts as planned; the promotion rate improved in 2 schools in Gaza Province, and the learning attitudes of students and teaching attitudes of teachers also improved. Thus, the project’s effectiveness and impact are high. As to the aspects of operation and maintenance (O&M), there were no serious problems in the technical aspect, but there were some problems in the institutional and financial aspects, as well as the O&M situations. Thus, sustainability of the project is fair. In the light of the above, this project is evaluated to be highly satisfactory.
Keywords: G - Mozambique / Moçambique; G - Rest of the World / Resto do Mundo; L - english / inglês; development partners / parceiros de cooperação; education / educação

EU & Partners' Country Roadmap for Engagement with Civil Society: 2016-2019 - Government of Canada; Government of Switzerland; UNICEF; USAID (Governments of Canada, Switzerland, UNICEF, USAID, 2015)
Study commissioned by EU and other countries on CSO engagement. The identification of priorities is based on four criteria: • The findings of the recent mapping of civil society in Mozambique commissioned by the EU and other studies; • The official EU guidance on the preparation of a civil society roadmap; • Existing and planned EU interventions and of the partners engaged in the roadmap; • The need to combine a longer term perspective with concrete actions over the next 3 years. The priorities constitute primarily a common agenda that will shape and orient discussions and collaboration between the roadmap partners. It allows situating individual interventions in a broader collective framework and as such adds a strategic dimension to programming.
Keywords: #Policy Document / Documento de Política; G - Mozambique / Moçambique; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação

PEDEC-NACALA Final Study Report Analysis Report: Strategic Master Plan on Strengthening of Nacala Corridor Region-Wide Freight Network for Agricultural and Mining Sectors - Oriental Consultants Global Co., Ltd.; RECS International Inc.; International Development Center of Japan Kokusai Kogyo Co., Ltd. (Japan International Cooperation Agency (JICA), 2015)
This document was prepared as an analysis report for sharing a study result on a particular theme as part of ‘The Project for Nacala Corridor Economic Development Strategies (PEDEC-Nacala)’ which is a technical assistance project supported by Japan International Cooperation Agency (JICA) for the Government of Mozambique. PEDEC-Nacala formulated integrated development strategies for corridor development by an integrated approach involving several sectors and also by giving consideration to environmental and social aspects. The actual strategies formulated in PEDEC-Nacala and details of the present situation of the Nacala Corridor Region are compiled into the PEDEC-Nacala Final Study Report
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; agriculture / agricultura; development partners / parceiros de cooperação; extractive industries / indústrias extractivas; infrastructure / infrastrutura

Nacala Transport Corridor Phase III: Executive Summary Environmental and Social Impact Assessment - Ali, Aymen A Osman (African Development Bank, 2012)
The Government of Mozambique (GoM), acting through the national roads administration (ANE) has made requests to international financial institutions including the African Development Bank, for the improvement of transport infrastructure and for strengthening the institutional capacity of the roads sector. ANE plans to apply a portion of these funds to the environmental and social impact assessment (ESIA) of the project for the rehabilitation of the N13, Cumanba-Mandimba-Lichinga (302 km). The road passes through many small towns and villages and is divided into three sections namely, Cuamba-Mandimba: 148 km (flat terrain), Mandimba-Lichinga148 km: (winding terrain, with some mountainous areas reaching about 1,400m in Lichinga) and MandimbaMalawi Border: 6 km (winding terrain). The N13 is part of two corridors: Nacala –N13/N1and Lichinga – N14/N1 providing a strategic link with the border of Malawi in Mandimba, the ports of Nacala and Pemba in the provinces of Nampula and Cabo Delgado respectively. The road also has the potential to contribute towards poverty reduction and stimulate the development of the country. The road is in fair conditions during the dry season but deteriorates during the rainy season due to poor drainage system and soil erosion. The width of the road varies between 5 and more than 10m and is usually lower than the surrounding terrain.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; GP - Nampula; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura; urbanization / urbanização

The Preparatory Survey on Nacala Port Development Project in the Republic of Mozambique Final Report - JICA (Japan International Cooperation Agency (JICA), 2011)
Japan International Cooperation Agency (JICA) decided to conduct the preparatory survey on Nacala Port Development Project in the Republic of Mozambique, and organized a survey team headed by Dr. Kobune of Ides and consists of OCDI, Oriental Consultants, ECOH CORPORATION, and Ides between June, 2010 and April, 2011. The survey team held a series of discussions with the officials concerned of the Government of the Republic of Mozambique, and conducted field investigations. As a result of further studies in Japan, the present report was finalized. I hope that this report will contribute to the promotion of the project and to the enhancement of friendly relations between our two countries. The Study Team compiled this report, which proposed the Medium and Long-term Development Plan of Nacala Port with the target year of 2030 and the Short-term Development Plan, and selected the Urgent Rehabilitation Project through close consultations with officials of the Mozambique Government, in particular, Ministry of Transport and Communications (MTC), Portos e Caminhos de Ferro de Mocambique E.P. (CFM), as well as the Management of Corredor de Desenvolvimento do Norte (CDN), and authorities concerned.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Health Commodity Security Project - World Bank (World Bank, 2010)
Information document about the Health Commodity Security Project. It is divided in the sections below: - Country and Sector Background - Objectives - Rationale for Bank Involvement - Description - Financing - Implementation - Sustainability - Lessons Learned from Past Operations in the Country/Sector - Safeguard Policies (including public consultation) - List of Factual Technical Documents - Contact point - For more information contact
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação; health / saúde

Ex-Post Evaluation Report of Grant Aid Projects 2009 (Mozambique) - JICA (Japan International Cooperation Agency (JICA), 2010)
Ex-post evaluation of ODA projects has been in place since 1975 and since then the coverage of evaluation has expanded. Japan’s ODA charter revised in 2003 shows Japan’s commitment to ODA evaluation, clearly stating under the section “Enhancement of Evaluation” that in order to measure, analyze and objectively evaluate the outcome of ODA, third-party evaluations conducted by experts will be enhanced. This volume shows the results of the ex-post evaluation of Grant Aid projects that were mainly completed in fiscal year 2006. The ex-post evaluation was entrusted to external evaluators to ensure objective analysis of the projects’ effects and to draw lessons and recommendations to be utilized in similar projects.
Keywords: G - Mozambique / Moçambique; L - english / inglês; development partners / parceiros de cooperação

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Final Report 1 of 3 Summary - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part I-II - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors).
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-IV - JICA (Japan International Cooperation Agency (JICA), 2010)
The Study Road (N13: Cuamba – Mandimba – Lichinga), as part of the two Mozambican corridors (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors), provides a strategic link to the Malawi Border at Mandimba with the ports of Nacala and Pemba, in Nampula and Cabo Delgado Provinces respectively. Although the Study Road has much potential for stimulating development and reducing poverty throughout the entire northern area of Mozambique by enabling efficient connection, the section concerned is the only unpaved section. The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part III-V - JICA (Japan International Cooperation Agency (JICA), 2010)
The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. The Study also determines the impact of providing an all-weather road on poverty reduction and environment. And establishment of the “Regional Development Program” intended for Niassa Province is also the objective of the Study. This program aims to extend the improvement effect to the wide area in conjunction with the road improvement (Nacala N13/N1 and Lichinga-Pemba N14/N1 corridors)
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Study on Road Improvement Plan in Nacala Development Corridor (n13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique Final Report 2 of 3 Main Text Part VI: Environmental and Social Considerations - JICA (Japan International Cooperation Agency (JICA), 2010)
In response to the request from the Government of the Republic of Mozambique, the Government of Japan decided to conduct the Preparatory Survey on Road Improvement Plan in Nacala Development Corridor (N13: Cuamba-Mandimba-Lichinga) and entrusted the study to the Japan International Cooperation Agency (JICA). Objectives of the study: (1) The objectives of the Study are to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing Cuamba – Lichinga road to an all-weather road for easier transit. (2) Formulation and recommendation of the “Regional Development Program” intended for Niassa Province is also the objective of the Study.
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part IV Economic Feasibility Study - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter1 Existing Traffic Flow Patterns This chapter aims to analyze traffic flow patterns on the Study Road based on various information in order to conduct the appropriate traffic demand forecast. Chapter 2 International Goods Transportation Though Nacala Corridor This chapter aims to discuss the current condition of international goods transportation through Nacala Corridor in order to estimate future traffic demand on the Study Road. Chapter 3 Traffic Demand Forecast 3.1 Macro-Economic Background 3.2 Forecasting Methods 3.3 Traffic Demand Forecast 3.4 Results of Traffic Forecast Chapter 4 Economic and Financial Analysis (Cuamba-Mandimba Section) The Study objective is “to determine the most technically feasible and economically viable, environmentally acceptable and socially optimal option of upgrading the existing earth/ gravel roads in the rural areas to paved roads.” For the purpose of the economic evaluation, it is important to first define the existing state of the Project road for the base case, and then to define the alternatives to be analyzed, and finally the structure of the analysis.
Keywords: G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

The Preparatory Survey on Road Improvement Plan in Nacala Development Corridor Final Report (N13: Cuamba-Mandimba-Lichinga) in the Republic of Mozambique: Part V Cross-Border Facilities - JICA (Japan International Cooperation Agency (JICA), 2010)
Chapter 1 Mozambique-Malawi Border Control and Facilities 1.1 Current Condition of Cross-Border Traffic between Mozambique and Malawi 1.2 Border Facilities between Mozambique and Malawi 1.3 Border Control System and Border Facilities Chapter 2 Mandimba Border Control and Facilities 2.1 Characteristics of Mandimba Border Area 2.2 Cross-Border Traffic and Cargo 2.3 Mandimba Border Post and Facilities 2.4 Chiponde Border Post and Facilities Chapter 3 Strategy for Upgrading Border Control and Facilities 3.1 SADC-COMESA Regional Strategy 3.2 One Stop Border Posts 3.3 Mozambique-Malawi Bilateral Strategy Chapter 4 Implementation Approach for Upgrading Mandimba Border Facilities 4.1 Needs Assessment and Proposed Approach for Implementation 4.2 Methodology for OSBP Phased Introduction 4.3 Challenges to OSBP Introduction Chapter 5 Border Development Strategy for Upgrading Mandimba Border Facilities 5.1 Traffic Demand Forecast at Mandimba-Chiponde Border 5.2 Proposed Implementation Policy 5.3 Proposed Facility Planning for Phased Introduction of OSBP
Keywords: *tagged; G - Mozambique / Moçambique; G - Nacala; G - north / norte; L - english / inglês; development partners / parceiros de cooperação; infrastructure / infrastrutura

Doing Business with the Ladies: Gender, Legal Reform, and Entrepreneurship in the International Finance Corporation - Bedford, Kate (Labour, Capital and Society / Travail, capital et société, 2009)
Since 2007 the World Bank's gender approach has moved away from the Wolfensohn-era emphasis on gender as central to social development concerns, towards a business case model that involves a far greater role for the private sector in efforts to reduce poverty and achieve gender equity. Using a case study of the International Finance Corporation (IFC) and its project, 'Doing Business', to promote the ease of doing business across the world, I ask what this new direction entails for the Bank's gender and development efforts, and examine the new links being forged between gender empowerment and free market reform. The article focuses on three themes in this regard: first, how attention to gender within the 'Doing Business' project helps promote labour market deregulation; second, the contested way in which free markets, legal reform, and gender equality are linked together; and third, the regional reconfigurations of Gender and Development (GAD) evident in the project's report on Women in Africa, wherein women entrepreneurs are celebrated and new networb of GAD specialists are drawn together.
Publisher: Labour, Capital & Society
Keywords: *indexed; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; development partners / parceiros de cooperação; entrepreneurship / empreendedorismo; gender / género; law / direito; ⛔ No DOI found